GAMYBINĖS LINIJOS, NAUDOJANT DUOMENŲ SURINKIMO SISTEMĄ, EFEKTYVUMO TYRIMAS - Donatas Dervinis (Taikomieji Moksliniai Tyrimai)
This article presents a methodology for evaluating the efficiency of a conveyor-based production line in the textile industry using an automated data collection system. The primary goal of the study is to assess production performance through real-time data acquisition and analysis. The developed approach enables efficiency measurement through two alternative methods: analyzing individual worker productivity and evaluating the overall production line output.